Origins of overshoots in the exciton spin dynamics in semiconductors - Ungar, Florian; Cygorek, Moritz; Vollrath, Martin Axt (arXiv.org, 2019)
We investigate the origin of overshoots in the exciton spin dynamics after resonant optical excitation. As a material system, we focus on diluted magnetic semiconductor quantum wells as they provide a strong spin-flip scattering for the carriers. Our study shows that overshoots can appear as a consequence of radiative decay even on the single-particle level in a theory without any memory. The magnitude of the overshoots in this case depends strongly on the temperature as well as the doping fraction of the material. If many-body effects beyond the single-particle level become important so that a quantum-kinetic description is required, a spin overshoot appears already without radiative decay and is much more robust against variations of system parameters. We show that the origin of the spin overshoot can be determined either via its temperature dependence or via its behavior for different doping fractions. The results can be expected to apply to a wide range of semiconductors as long as radiative decay and a spin-flip mechanism are present.